Educational Governance Today - BEHRENS, CHRISTOPH (Jurnal Studi Pemerintahan, 2014)
In the communication and knowledge based globalvillage, under the conditions of dynamic Change inan economy driven world, education has become acomplex and challenging endeavor, both for individualsand organizations. Learning has changeddramatically: knowledge and skills are quickly outdatedand devaluated, giving education a new meaningwithin an individual biography; schools, universitiesand other providers of education go throughorganizational revolutions, who are challenging theirself-concept and management; governments areunder pressure to reshape Educational Governanceaccording to new paradigms with the overall goalto sustain national or regional competitiveness. Arekey actors in the education system ready to face thesechallenges and to modernize their organizations?Starting from an overview on the Complexity of Learningin modern societies, generalizable consequencesare reviewed in a case study on Germany. It leads toa framework for a necessary research project incountries such as Indonesia, which are still aheadof educational reform. The focus is on the organizationalmeso and macro level that is playing the keyrole in Educational Governance.Keywords: Change Management, DemographicChange, Educational Governance, Globalization